The Sex Education Method in Agrarian Communities - Desriani, Desriani; Muthohar, Sofa; Filasofa, Lilif Muallifatul Khorida; Mursid, Mursid (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
The purpose of this study was to describe how an agrarian society provides sex education. This research was conducted based on the assumption that parents need to teach sex education to early childhood, even though it is taboo, but in a good way. This research is qualitative research with an ethnographic research type. The results showed that 1) The community uses fiqh (rituals of worship) learning methods to cover genitalia and teach the culture of shame from an early age. 2) people are still taboo to mention genitals directly so that they use other terms that are considered not to stimulate crime and are more polite, namely to refer to the penis as sunik, gentog and anu, while for the vagina is replaced with the term memek, iwak kebo and anu. 3) people still use the circumcision method for women even though WHO has stated it is prohibited. This study recommends the government and community leaders to continue to carry out sex education for children with the correct method according to health, religious, and human rights laws.